2015
DOI: 10.1214/15-aoas852
|View full text |Cite
|
Sign up to set email alerts
|

Joint modeling of longitudinal drug using pattern and time to first relapse in cocaine dependence treatment data

Abstract: An important endpoint variable in a cocaine rehabilitation study is the time to first relapse of a patient after the treatment. We propose a joint modeling approach based on functional data analysis to study the relationship between the baseline longitudinal cocaineuse pattern and the interval censored time to first relapse. For the baseline cocaine-use pattern, we consider both self-reported cocaineuse amount trajectories and dichotomized use trajectories. Variations within the generalized longitudinal trajec… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Yao (2007) proposed a shared latent process model. Yan et al (2017) proposed a shared random effect model with a two-step estimation, and Ye et al (2015) proposed a model for baseline longitudinal patterns and interval-censored event time data. To clarify, joint modeling here refers to the situation where the domain of function is longitudinal time.…”
Section: Introductionmentioning
confidence: 99%
“…Yao (2007) proposed a shared latent process model. Yan et al (2017) proposed a shared random effect model with a two-step estimation, and Ye et al (2015) proposed a model for baseline longitudinal patterns and interval-censored event time data. To clarify, joint modeling here refers to the situation where the domain of function is longitudinal time.…”
Section: Introductionmentioning
confidence: 99%
“…They revealed that it is often the changing patterns of the longitudinal outcome, rather than the actual value at the moment of event, that affects a patient's survival risk. In the following studies, the model was further extended for partial follow‐up studies, interval‐censored time, and prediction . However, these models focus on a single longitudinal outcome and are not applicable to the studies of neurodegenerative diseases, such as AD, which collect multiple longitudinal measures with more complexity.…”
Section: Introductionmentioning
confidence: 99%
“…Li et al [10] propose a bivariate functional model mixed with a skewed continuous variable and a binary measurement. Ye et al [11] discuss a jointly modeling framework for a functional data response and a time-to-event outcomes. Tidemann-Miller et al [12] propose a multivariate mixed-response functional data model.…”
Section: Introductionmentioning
confidence: 99%